Current Statement of Intensive Care Units in Turkey: Data obtained from 67 Centers - (:unkn) unknown (BILIMSEL TIP PUBLISHING HOUSE, 2018)
OBJECTIVES: We aimed to obtain information about the characteristics of the ICUs in our country via a point prevalence study. MATERIAL AND METHODS: This cross-sectional study was planned by the Respiratory Failure and Intensive Care Assembly of Turkish Thoracic Society. A questionnaire was prepared and invitations were sent from the association's communication channels to reach the whole country. Data were collected through all participating intensivists between the October 26, 2016 at 08:00 and October 27, 2016 at 08:00. RESULTS: Data were collected from the 67 centers. Overall, 76.1% of the ICUs were managed with a closed system. In total, 35.8% (n=24) of ICUs were levels of care (LOC) 2 and 64.2% (n=43) were LOC 3. The median total numbers of ICU beds, LOC 2, and LOC 3 beds were 12 (8-23), 14 (10-25), and 12 (8-20), respectively. The median number of ventilators was 12 (7-21) and that of ventilators with non-invasive ventilation mode was 11 (6-20). The median numbers of patients per physician during day and night were 3.9 (2.3-8) and 13 (9-23), respectively. The median number of patients per nurse was 2.5 (2-3.1); 88.1% of the nurses were certified by national certification corporation. CONCLUSION: In terms of the number of staff, there is a need for specialist physicians, especially during the night and nurses in our country. It was thought that the number of ICU-certified nurses was comparatively sufficient, yet the target was supposed to be 100% for this rate.
Keywords: Intensive care unit; point prevalence; survey; ICU; RECOMMENDATIONS; STANDARDS; MORTALITY; MEDICINE; OUTCOMES